LAW DEPARTMENT STUDENTS’ ATTITUDE AND MOTIVATION IN LEARNING ENGLISH AS FOREIGN LANGUAGE - Arwin Arwin (Yayasan Akrab Pekanbaru, 2019)
This study investigates non-English major students’ attitude and motivation towards learning English as foreign language at Law Department Halu Oleo University. This study also expected to find out what gender is more motivated towards learning English. The study employed the descriptive design. The total sample of this study was 130 students and registered in academic years of 2018/2019. The sample investigated using attitude and motivation questionnaires 5-point Likert Scale that adopted from AMTB by Gardner. The result of this study indicates that: (1) the participants have positive attitude towards learning English as foreign language. (2) The level of participants’ motivation as sample of this study is high. (3) The integrative motivation is more dominant than instrumental motivation. (4) Female is more motivated than male students. Most of those surveyed held positive views of the development English teaching towards non-English major students. The English lecturer is highly expected to be more commitment with the schedule of teaching and learning process. An effective number of students in a class are still need high consideration. The findings of this study may help language developers, syllabus designers and decision makers to develop programs and design syllabi and create interesting textbooks which maintain students' positive attitude and motivation.